Integration of Massive Open Online Course (MOOC) in Ophthalmic Skills Training for Medical Students: Outcomes and Perspectives. Issue 6 (7th November 2022) - Huang, Zijing; Yang, Jianling; Wang, Hongxi; Chen, Binyao; Zheng, Dezhi; Chen, Haoyu
Abstract : Purpose: To integrate a massive open online course (MOOC) into conventional clinical ophthalmology teaching and investigate its impact on the skills of medical students. Methods: This was a nonrandomized, prospective, and comparative study. Seventy-six medical students were assigned to 2 groups before their clinical teaching. Some were asked to follow a MOOC for slitlamp microscope examination but used textbook for preview of visual acuity test (SLMM group, n=39), while others were required to take a MOOC for visual acuity test and previewed slitlamp microscopy using textbook (VATM group, n=37). All the students then underwent conventional clinical ophthalmology teaching on slitlamp microscopy and visual acuity test. Their performance was evaluated using Direct Observation of Procedural Skills (DOPS). Students were also asked to complete a 5-item questionnaire about their learning experience and comment on the MOOC. Results: Students in the SLMM group obtained overall higher scores in the slitlamp practical skills (47.64±4.01 vs 44.68±5.99, P =0.013), while those in the VATM group performed better in the visual acuity test (46.45±4.90 vs 43.78±4.94, P =0.004). MOOC was deemed to increase learning interests (4.13 of 5 points) and motivation (4.01 of 5 points) but was more preferred as an additional tool to traditional teaching methods (4.34 of 5 points) rather than to replace them (2.92 of 5 points). Conclusions: MOOC offers an added benefit in improving clinical skills and is worth advocating as an additional tool for clinical ophthalmic education.